REFORMASI MENUJU LOCAL GOVERNMENT COUNCIL YANG BERKUALITAS (REFORM TOWARD QUALITY OF LOCAL GOVERNMENT COUNCIL) - Mustofa, Amirul (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Political reform has occurred in Indonesia, namely when the regime transition of power from the old order to new order, and when the transition toward the new order has yet to reform the order form is of very local government councils. Local government councils according to the opinion of the writer has never showed good political performance, they simply just as political actors who seek personal gain or rent seeking, either the status quo as well as rent-seeking hunters.In connection with these conditions the local government councils is a form of democracy at local government level is very importance role in accommodating the aspirations of the community and promote development at the local level. Referring to this idea the authors approach the study of reform as the basic options that can be found those items essential for local government reform towards a quality council. Variables of important reforms that opinion writer are: Â minimize the number of political parties; amendment to the constitution need to be rethinking;political education to be a prerequisite determination of local government councils; and scope of work development of local government council.Key words: local government councils, policy reform, political parties